A novel CBL-B(flox/flox) mouse model allows tissue-selective fully conditional CBL/CBL-B double-knockout: CD4-Cre mediated CBL/CBL-B deletion occurs in both T-cells and hematopoietic stem cells - Goetz, Benjamin (Oncotarget, 2016)
CBL-family ubiquitin ligases are critical negative regulators of tyrosine kinase signaling, with a clear redundancy between CBL and CBL-B evident in the immune cell and hematopoietic stem cell studies. Since CBL and CBL-B are negative regulators of immune cell activation, elimination of their function to boost immune cell activities could be beneficial in tumor immunotherapy. However, mutations of CBL are associated with human leukemias, pointing to tumor suppressor roles of CBL proteins; hence, it is critical to assess the tumor-intrinsic roles of CBL and CBL-B in cancers. This has not been possible since the only available whole-body CBL-B knockout mice exhibit constitutive tumor rejection. We engineered a new CBL-B(flox/flox) mouse, combined this with an existing CBL(flox/flox) mouse to generate CBL(flox/flox); CBL-B(flox/flox) mice, and tested the tissue-specific concurrent deletion of CBL and CBL-B using the widely-used CD4-Cre transgenic allele to produce a T-cell-specific double knockout. Altered T-cell development, constitutive peripheral T-cell activation, and a lethal multi-organ immune infiltration phenotype largely resembling the previous Lck-Cre driven floxed-CBL deletion on a CBL-B knockout background establish the usefulness of the new model for tissue-specific CBL/CBL-B deletion. Unexpectedly, CD4-Cre-induced deletion in a small fraction of hematopoietic stem cells led to expansion of certain non-T-cell lineages, suggesting caution in the use of CD4-Cre for T-cell-restricted gene deletion. The establishment of a new model of concurrent tissue-selective CBL/CBL-B deletion should allow a clear assessment of the tumor-intrinsic roles of CBL/CBL-B in non-myeloid malignancies and help test the potential for CBL/CBL-B inactivation in immunotherapy of tumors.